Simulation of Agent-Based Negative Selection Model (ABNSM) for Reservoir Water Level Monitoring - Doi S.M.C.; Norwawi N.M.; Ismail R.; Wahab M.H.A.; Idrus S.Z.S. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA